Filling lateral canals: Influence of calcium hydroxide paste as a root canal dressing - Bruno Carvalho de Sousa; Fábio de Almeida Gomes; Cláudio Maníglia Ferreira; Diana Santana de Albuquerque (Wolters Kluwer Medknow Publications, 2013)
Context: The use of intracanal medication aims to provide antimicrobial activity in the root canal system, leading to a more satisfactory condition for root canal obturation. However, it is important to evaluate whether such medication would affect the sealing-off from the main root canal of ramifications such as lateral canals. Aim: Evaluate the influence of calcium hydroxide [Ca(OH) 2 ] paste on the filling of lateral canals. Settings and Design: Ex vivo quantitative laboratory study. Materials and Methods: Sixty single-rooted teeth with lateral canals created were used, 10 teeth per group. Group A was described respectively as lateral condensation technique (subgroup 1), thermomechanical compaction (subgroup 2), and continuous wave of condensation (subgroup 3). In Group B, subgroups 4, 5, and 6 were filled with Ca(OH) 2 for 7 days before filling using the techniques applied in subgroups 1, 2, and 3. Radiographic evaluation was performed to count the number of filled lateral canals in each group. The teeth were cross-sectioned over the lateral canals; thus, 180 specimens were obtained. Each specimen was immersed in a polyester resin. Digital images were obtained and specific software (Image Tool; ) was used to evaluate the number of obturated lateral canals and the filling length in each lateral canal of groups. Statistical Analysis Used: Data were statistically analyzed using SPSS 12.0 for Windows (Descriptive statistical analysis and Newman-Keuls test). Results: A greater number of simulated lateral canals were filled in Group A (91.1%). Group B had less filled lateral canals (33.3%). The sealing of lateral canals was statistically different between Group B (26.15%) and Group A (74.43%). Conclusions: According to the radiographic analysis and the linear filling measurement, the use of Ca(OH) 2 decreased the number and the length of sealed lateral canals.